Prevalence of metabolic syndrome and components in rural, semi-urban and urban areas in the littoral region in Cameroon: impact of physical activity - Nadine Carole Bilog; Jerson Mekoulou Ndongo; Elysée Claude Bika Lele; Wiliam Richard Guessogo; Peguy Brice Assomo-Ndemba; Ahmadou; Noel Babayana Etaga; Yves Julien Mbama Biloa; Josiane Gertrude Bwegne Ngasse Bindi; Abdou Temfemo; Samuel Honoré Mandengue; Jessica Guyot; et al. (Journal of Health, Population and Nutrition, 2023)
Abstract Background Living areas in developing countries impact seriously lifestyle by modifying energy consumption and energy expenditure. Thus, urbanization is associated with less practice of physical activity (PA), a leading cause of metabolic syndrome (MetS) which prevalence vary in African countries. The present study aimed to assess the effect of PA on MetS according to urbanization level in the littoral region, Cameroon. Methods A cross-sectional study was conducted in three geographical settings (urban, semi-urban, and rural) in the littoral region in Cameroon. A total of 879 participants were included (urban: 372, semi-urban: 195 and rural: 312). MetS was defined according to the International Federation of Diabetes 2009. The level of PA was assessed using the Global Physical Activity questionnaire. Results Low level of PA was (P < 0.0001) reported in urban (54.5%), semi-urban (28.7%) and rural (16.9%) and high level in rural area (77.9%). The prevalence of MetS was higher in urban areas (37.2%), then rural (36.8%) and finally semi-urban (25.9%). Hyperglycemia (p = 0.0110), low HDL-c (p < 0.0001) and high triglyceridemia (p = 0.0068) were most prevalent in urban residents. Participants with low level of PA were at risk of MetS (OR: 1.751, 95% CI 1.335–2.731, p = 0.001), hyperglycemia (OR: 1.909, 95% CI 1.335–2.731, p = 0.0004) abdominal obesity(OR: 2.007, 95% CI 1.389–2.900, p = 0.0002), low HDL-c (OR: 1.539, 95% CI 1.088–2.179, p = 0.014) and those with moderate level of PA were protected against high blood pressure(OR: 0.452, 95% CI 0.298–0.686, p = 0.0002) and compared to those with high level of PA. Urban dwellers were at the risk of MetS compared to rural residents (OR: 1.708, 95% CI. 1.277–2.285, p = 0.003) and protected against high blood pressure (OR:0.314, 95% CI 0.212–0.466, p < 0.0001), abdominal obesity (OR: 0.570, 95% CI 0.409–0.794, p = 0.0009), and low HDL-c (OR: 0.725, 95% CI 0.534–0.983, p = 0.038) compared to rural residents. Conclusions MetS was more prevalent in urban dwellers and was associated with a low level of PA.